Ecology of Land Cover Change in Glaciated Tropical Mountains - Young, Kenneth R. (2014)
Tropical mountains contain unique biological diversity, and are subject to many consequences of global climate change, exasperated by concurrent socioeconomic shifts. Glaciers are in a negative mass balance, exposing substrates to primary succession and altering downslope wetlands and streams. A review of recent trends and future predictions suggests a likely reduction in areas of open habitat for species of high mountains due to greater woody plant cover, accompanied by land use shifts by farmers and pastoralists along the environmental gradients of tropical mountains. Research is needed on the biodiversity and ecosystem consequences of successional change, including the direct effects of retreating glaciers and the indirect consequences of combined social and ecological drivers in lower elevations. Areas in the high mountains that are protected for nature conservation or managed collectively by local communities represent opportunities for integrated research and development approaches that may provide ecological spaces for future species range shifts.